People and Computers XIX — The Bigger Picture
DOI: 10.1007/1-84628-249-7_15
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Evolution of HCI

Abstract: A study of the evolution of the HCI community is described based on information extracted from leading HCI journals. The study includes a traditional author co-citation analysis and a progressive domain visualization of a co-authorship network of 3,620 authors and a 1,038-node hybrid network of topical terms and cited articles. Emerging trends and prominent patterns of these networks are identified and compared with an existing survey of the field. The study contributes to the understanding of HCI at a macrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…By examining other emerging trends, we expect to improve our understanding of the roots of HCI." (Chen et al, 2005) Once the cornerstones were defined, Chen and Panjwani continued to define 7 cannons of HCI: 1) Knowledge representation and problem solving methods, 2) the world wide web, 3) ubiquitous computing and context-aware computing, 4) usability evaluation, 5) user centered design, 6) perceptual control, 7) enterprise resource planning.…”
Section: Origins Of Human Computer Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…By examining other emerging trends, we expect to improve our understanding of the roots of HCI." (Chen et al, 2005) Once the cornerstones were defined, Chen and Panjwani continued to define 7 cannons of HCI: 1) Knowledge representation and problem solving methods, 2) the world wide web, 3) ubiquitous computing and context-aware computing, 4) usability evaluation, 5) user centered design, 6) perceptual control, 7) enterprise resource planning.…”
Section: Origins Of Human Computer Interactionmentioning
confidence: 99%
“…"This is a relatively small area compared with the others…Taylor 1988 appears to be a main connection between this area and the core HCI; the article was about layered protocols for computerhuman dialogue." (Chen et al, 2005) More recently Carrol ( 2001) identified 4 roots of HCI and suggested fusing these roots together can drive the evolution of HCI. These for are: 1) protyping and iterative development from software engineering, 2) software psychology and human factors of computing systems, 3) user interface software from computer graphics, and finally 4) models, theories, and frameworks from cognitive science.…”
Section: Origins Of Human Computer Interactionmentioning
confidence: 99%